Efficient one-pot synthesis of the unexpected fused multicyclic iminosugars by an aza-Diels–Alder mechanism. Issue 23 (12th October 2022) - Wu, Jilai; Su, Lulu; Jia, Tongguan; Xu, Xiaoming; Cui, Yaxin; Wei, Chao; Li, Xiaoliu; Chen, Hua
Abstract : A simple and efficient one-pot protocol has been developed by an aza-Diels–Alder mechanism for the stereoselective synthesis of novel fused multicyclic iminosugars with structural diversity. Abstract : A simple and efficient one-pot synthesis has been developed firstly by an aza-Diels–Alder mechanism for the stereoselective synthesis of novel fused multicyclic iminosugars with structural diversity. The adaptability of this method has been demonstrated by using a variety of aromatic amines and tosylated sugars.